The Urgency of Establishing a National Digital Commission to Ensure Responsive and Sustainable Cyber Governance in Indonesia (International Forum of Researchers and Lecturers, 2025)
The rapid development of information and communication technology has brought significant changes to social, economic, and political life in Indonesia. However, the complex and rapidly changing dynamics of cyberspace present major challenges in statute, personal data protection, disinformation, and cybersecurity. Unfortunately, the existing regulatory framework is still sectoral and has not yet responded holistically to the various digital issues that arise. This fragmented approach often leads to overlapping authorities, inconsistent enforcement, and gaps in addressing emerging cyber threats. Therefore, the establishment of the National Digital Commission is urgently needed as an independent institution tasked with coordinating, formulating, and overseeing digital policies in an integrated and systematic manner. This commission should consist of multidisciplinary experts in law, technology, and public policy, ensuring balanced perspectives in policy formulation. In addition, it should serve as a bridge between the government, the private sector, and civil society to facilitate inclusive and transparent digital governance. The National Digital Commission is expected to ensure cyberspace governance that is responsive to technological developments while maintaining digital resilience. It must also actively promote digital literacy, ethical online behavior, and responsible use of social media platforms to combat hoaxes and hate speech. Furthermore, the commission must strengthen Indonesia’s cybersecurity infrastructure to protect national interests and uphold the rights of its citizens in the digital space. By creating a unified regulatory framework and robust oversight mechanism, Indonesia can build a safer and more democratic digital ecosystem. This effort is essential in reinforcing accountability, defending cybersecurity, advancing democracy, ensuring governance, and safeguarding innovation in the face of rapid digital transformation.